Fluoroquinolone heteroresistance, antimicrobial tolerance, and lethality enhancement - Singh, Amit; Zhao, Xilin; Drlica, Karl (Frontiers in Cellular and Infection Microbiology, 2022)
Two general approaches are discussed for reducing the progression of MDR-TB to XDR-TB. One involves early detection of fluoroquinolone heteroresistance to allow treatment modification that will suppress enrichment of resistant organisms. Rapid DNA-based methods to detect resistant subpopulations exploit the finding that resistance mutations occur largely in a few codons of DNA gyrase. Two types of heteroresistance occur, mixed infections and clonal infections. The former indicates inadequate infection control; the latter indicates inadequate treatment of individual patients. The second approach for controlling MDR-TB involves understanding fluoroquinolone lethality well enough to find ways to enhance killing. Studies with Escherichia coli provide guidance: lethal action, which is mechanistically distinct from blocking growth, is associated with a surge in respiration and reactive oxygen species (ROS). Mutations in carbohydrate metabolism that attenuate ROS accumulation create pan-tolerance to antimicrobials, disinfectants, and environmental stressors. These observations indicate the existence of a general death pathway with respect to stressors. Mycobacterium tuberculosis displays a variation on the death pathway idea, as ROS is generated by NADH-mediated reductive stress rather than by respiration. Nevertheless, respiration and additional ROS accumulation can be stimulated by addition of N-acetyl cysteine, thereby enhancing moxifloxacin lethality with M. tuberculosis in culture, during infection of cultured macrophages, and with infection of mice. The work has several implications. First, detection methods for M. tuberculosis heteroresistance can be used to suppress/slow the emergence of fluoroquinolone resistance. Second, the discovery of pan-tolerance with E. coli raises the novel idea that massive use of disinfectants will erode antimicrobial effectiveness. Third, addition of ROS stimulators, such as N-acetyl cysteine, to fluoroquinolone treatment of tuberculosis offers a new direction for suppressing the transition of MDR-TB to XDR-TB. Fourth, ROS action increases the rate of killing but not the extent; thus, the dosing interval is likely to be important.